The impact of genetic modified Ma bamboo on soil microbiome - Wang, Kai; Liu, Mengxia; Cai, Changyang; Cai, Shifeng; Ma, Xiangqing; Lin, Chentao; Zhu, Qiang (Frontiers in Microbiology, 2022)
Evaluating the potential alteration of microbial communities is a vital step for biosafety of genetic modified plants. Recently, we have produced genetic modified Ma bamboo with increased cold and drought tolerance by anthocyanin accumulation. In this work, we aim to study the potential effects on microbial communities in rhizosphere soils during the cultivation of genetic modified bamboo. Rhizosphere and surrounding soil were collected at 3-month post-transplant. The amplicon (16S rDNA and ITS1) were sequenced for analysis of bacterial and fungal communities. Multiple software and database (Picrust2, FAPROTAX and FUNGulid) were applied to predict and compare the microbial functions involving basic metabolisms, nitrogen usage and presence of plant pathogens. There were no substantial change of the structure and abundance of rhizosphere soil microbial communities between genetic modified and wild type bamboo. For the surrounding soil, the bacterial biota α-diversity increased (chao1: 1001±80 to 1276±84, observed species: 787±52 to 1194±137, PD whole tree: 75±4 to 117±18) and fungal biota α-diversity decreased (chao1: 187±18 to 145±10) in samples of genetic modified bamboo compared to those of wild type bamboo. The microbiota predicted functions did not change or had no negative alteration between genetic modified and wild type bamboo, in both rhizosphere and surrounding soils. As a conclusion, the growth of genetic modified bamboo had no substantial change on rhizosphere soil microbial communities, while minor alteration on bamboo surrounding soil microbial communities with no harmful effects. Moreover, the genetic modified bamboo had no negative effect on the predicted functions of microbiota in soil.